2017
DOI: 10.1093/tropej/fmx038
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Weight Gain Patterns in Preterm Very-Low-Birth-Weight Infants Born in a Tertiary Care Center in South India

Abstract: The recommended growth velocity of 10-15 g/kg/day can be achieved using unfortified expressed breast milk, though at higher feeding volumes of 200 ml/kg/day. These centile curves can be useful for monitoring postnatal growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 22 publications
0
14
0
1
Order By: Relevance
“…The overall proportion of preterm with poor weight gain observed in this study was high. Furthermore the observed average weight gain is below the goal for preterm weight gain (≥ 15 grams/kg/day) estimated to replicate the growth velocity of a normal foetus during third trimester of pregnancy (4,(11)(12)(13)(14). Poor weight gain was observed more among early preterm compared to late preterm infants, although this was not statistically signi cant, it may be a re ection of poor feeding as a result of feeding intolerance and also the practice in our unit during the study period of delaying initiation of feeds for at least 24 hours for this category of neonates.…”
Section: Discussionmentioning
confidence: 99%
“…The overall proportion of preterm with poor weight gain observed in this study was high. Furthermore the observed average weight gain is below the goal for preterm weight gain (≥ 15 grams/kg/day) estimated to replicate the growth velocity of a normal foetus during third trimester of pregnancy (4,(11)(12)(13)(14). Poor weight gain was observed more among early preterm compared to late preterm infants, although this was not statistically signi cant, it may be a re ection of poor feeding as a result of feeding intolerance and also the practice in our unit during the study period of delaying initiation of feeds for at least 24 hours for this category of neonates.…”
Section: Discussionmentioning
confidence: 99%
“…The mean weight velocity in our study group of infants is 11.24 gm/kg/day, though lower as compared to Fenton charts, is consistent with the studies in Indian literature. 15,18 Since the babies recovered well and were discharged the mean positive weight velocity is encouraging. The wide range over which the weight velocity is spread is due to multiple factors, prominent amongst them being gestational age, weight <1000 gm, associated morbidities, delayed readiness for enteral feeds and non-fortification of the feeds.…”
Section: Discussionmentioning
confidence: 86%
“…When mean weight was compared statistically at different time intervals among the study subjects, it was found to be statistically significant. Mathew et al in their study revealed that mean birth weight±SD was 1226.76±191 [26]. Mean time (±SD) to reach full volume feeds was 8.66±2.6 days.…”
Section: Discussionmentioning
confidence: 91%